2018
DOI: 10.3168/jds.2018-14663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rumen-protected B vitamins and choline supplementation on health, production, and reproduction in transition dairy cows

Abstract: The objectives were to determine the effects of a rumen-protected blend of B vitamins and choline (RPBC) on the incidence of health disorders, milk yield, and reproduction in early lactation and the effects on gene expression and liver fat infiltration. A randomized controlled trial in 3 commercial dairy herds (n = 1,346 cows with group as the experimental unit; experiment 1) and a university research herd (n = 50 cows with cow as the experimental unit; experiment 2) evaluated the use of 100 g/cow per d of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
11
0
3
Order By: Relevance
“…Los indicadores de integridad del tejido hepático (AST, GGT y GD), junto con los niveles de BHB medidos en las vacas de este estudio se encontraban cercano al límite superior de referencia (0,64 y 0,67 mmol L -1 para CPR y control respectivamente) y fueron disminuyendo posterior al parto (0,73 a 0,61 mmol L -1 para las SRP +1 y +3), sugiriendo que tanto las vacas suplementadas con CPR como las del grupo control no presentarían cuadros de cetosis o hígado graso. Resultados similares obtuvieron Morrison et al (2018) quienes observaron una disminución en las concentraciones de BHB de 0,67 a 0,61 y de 0,67 a 0,62 para vacas con y sin suplementación, respectivamente. Adicionalmente, no observaron diferencias en la proporción de vacas con niveles de BHB por sobre los 1,2 mmol L -1 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Los indicadores de integridad del tejido hepático (AST, GGT y GD), junto con los niveles de BHB medidos en las vacas de este estudio se encontraban cercano al límite superior de referencia (0,64 y 0,67 mmol L -1 para CPR y control respectivamente) y fueron disminuyendo posterior al parto (0,73 a 0,61 mmol L -1 para las SRP +1 y +3), sugiriendo que tanto las vacas suplementadas con CPR como las del grupo control no presentarían cuadros de cetosis o hígado graso. Resultados similares obtuvieron Morrison et al (2018) quienes observaron una disminución en las concentraciones de BHB de 0,67 a 0,61 y de 0,67 a 0,62 para vacas con y sin suplementación, respectivamente. Adicionalmente, no observaron diferencias en la proporción de vacas con niveles de BHB por sobre los 1,2 mmol L -1 .…”
Section: Discussionunclassified
“…En teoría, fue planteado que la suplementación con CPR podría incrementar la concentración de grasa y proteína en la leche al favorecer el transporte y utilización de lípidos en la glándula mamaria y las mayores concentraciones de caseína asociadas a una mayor disponibilidad de metionina (Jayaprakash et al, 2016). No obstante, esta ventaja teórica no se ha reflejado en otros estudios (Piepenbrink y Overton, 2003;Morrison et al, 2018), lo que concuerda con nuestros resultados.…”
Section: Producción Y Composición De La Lecheunclassified
See 1 more Smart Citation
“…Supplements include targeted use of choline, B-vitamins (Duplessis and others 2014, Morrison and others 2018), and oral supplementation of monensin (Petersson-Wolfe and others 2007). A meta-analysis summarising 17 studies of monensin use in lactating cattle showed an overall decreased risk of ketosis in treated cattle (Duffield and others 2008).…”
Section: Ketosismentioning
confidence: 99%
“…of B vitamins, reported elsewhere (Morrison, 2017). All farms used automated activity monitors for estrus detection as the primary means of reproductive management, supplemented by synchronization for timed AI.…”
Section: Short Communication: Associations Of Udder Edema With Healthmentioning
confidence: 99%